Geriatrics emergency medicine – the need of time - Khan, Naheed Habibullah; Kothari, Sarah Afzal; Shahan Waheed (Journal of the Pakistan Medical Association, 2023)
Madam, Since the inception of Emergency Medicine (EM) in Pakistan, it has been an ever-growing field, and one such current need is the development of geriatric emergency care. Older patients have a longer Emergency department (ED) stays and more frequent admissions, with an increased risk of special care and intensive care admissions. These patients have unusual presentations and multiple comorbidities, are more prone to complications, are easily affected by their surroundings and require an understanding of their social needs and thorough counselling, complicating their care. The elderly population also termed the ‘silver tsunami’ shares a significant burden of the ED in Pakistan.1 According to the 2017 national census, nearly 13.7 million people in Pakistan, were over the age of 60, accounting for roughly 7% of the total population,2 which is anticipated to double in the coming years, increasing the burden of geriatric patients. This highlights the urgent need todevelop a specialised system for the elderly in acute care settings. Although several programmes in Pakistan focus on elderly care under Family Medicine, there remains a huge gap in emergency care, which is crucial in providing 24/7 healthcare service delivery. Geriatrics curriculum must be incorporated in emergency medicine residency programmes to facilitate patient outcomes, decrease mortality, and prevent functional decline in that age group. The American College of Emergency Physicians (ACEP) certified hospitals as "Geriatric Emergency Departments" (GEDs) in 2018 based on GED guidelines established in 2014. The purpose was to assist in providing more effective care to the elderly population. 3 According to Kaeley et al., a considerably higher number of older people (2965, 54.9%) were hospitalised from the ED, with approximately 651, or 21.9 % admitted to the intensive care unit.4 Geriatric Emergency Medicine Fellowship training provides EDs with expertise to meet the need of a growing geriatric population. (Figure 1) These programmes can serve as a foundation for clinical innovation, research, and education focusing on the elderly population. Work on this is being done globally., Pakistan must play a role in this aspect of emergency medicine, owing to the rapidly increasing older population and advancement in GEM practice worldwide.3,5 A proper healthcare infrastructure at the government level will help geriatric patients cope with limited health resources, financial burdens, and palliative care. A better understanding of geriatric care will assist us in better allocating and utilising the limited resources we have available to alleviate the financial burden. ---Continue